Experience in asteroid search using Astrometrica software - Ascencio Moran, Junior (2019)
The present work of this research consists of the analysis of telescopic images provided by the International Astronomical Search Collaboration (IASC) to find asteroids that can be named. The concern in searching for asteroids helps the scientific community that promotes the collaboration of young students and astronomy fans get experience in finding asteroids through campaigns related to these. The Space Generation Advisory Council (SGAC) campaign in partnership with IASC has found around 1500 asteroids since the beginning of October 2006 as each year more than 1000 teams from different countries participate. The Astrometrica software was used which is in charge of receiving the images in FITS format. The configuration of the selected telescope is carried out so that they are later analyzed in greater detail. Finally, a clean and precise Minor Planet Center (MPC) report is made, which is what the campaign requires so that it can go on to a preliminary phase and subsequently be accepted by the international astronomical union. The asteroids that become named will be registered in the catalog of official minor planets of the world. In the campaign related to this study, one finds 28 possible asteroids.